Ekspresi Temporal OsFTL5 pada Padi (Oryza sativa L. âCempo Irengâ dan âCempo Abangâ) - , NIWANDA RIZKI DEHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cempo Ireng has long harvest period which is 150-180 days after sowing therefore farmers are not interested in cultivating it. Cempo Ireng and Cempo Abang are local varieties of rice which are cultivated at Yogyakarta. They are known to be valuable for their high nutritional value because of ferrum, anthocyanin and other minerals content. Flowering time is triggered by endogen factors (genes and hormon) and exogen factors (photoperiod, nourishment, and temperature). Flowering genes expressed for triggering flowering phase that will end the transtition phase between vegetative and reproductive phase. The study of genes which are related to flowering time in this two cultivars of Indonesia local rices is needed. One of the flowering genes in rice is OsFTL5. The purpose of this research was to study the temporal gene expression of OsFTL5 in Cempo Ireng and Cempo Abang rice. This research included RNA isolation from leaves blade within 10 days interval, DNAse Treatment, cDNA synthesis, and amplification of Ubiquitin as internal control and OsFTL5. The results showed that the heading date of Cempo Ireng at 118 days after sowing (DAS) and for Cempo Abang was on 55 DAS. OsFTL5 in Cempo Ireng was expressed at 80, 91, 100, 109, 120, and 130 DAS, meanwhile OsFTL5 in Cempo Abang was expressed at 40, 51, 60, and 70 DAS. The expression of OsFTL5 was also expressed after heading date in both cultivar.